MATHEMATICAL LEARNING MOTIVATION OF SUBMISSION AND REDUCTION OF PARTICIPANTS IN PRIMARY SCHOOL USING REALISTIC MATHEMATICS EDUCATION (RME) - Dodi Ardiansah; Mia Yusmianti; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2019)
This study aims to explain the application of realistic mathematics education in addition and subtraction mathematics learning in class III of SDN 1 Sudimampir, one of the low motivation of students to learn mathematics addition and subtraction is caused by learning activities that are more teacher-centered, so students are less actively involved in the learning process and result in monotonous learning activities in the classroom. Based on the above problems, improvements can be made to increase motivation to learn mathematics using realistic mathematics education. population and sample in the study focused on class III students, the method used in this study was the experimental method. The data collection technique is to provide learning and working on the problem, then grouping values based on the results of student performance in working on mathematical questions, arranged based on group distribution data for more specific value distribution into the mean median mode and graphs in order to find out the results of applying realistic mathematical methods education is expected to increase students 'motivation to learn mathematics, from the study there was a significant increase in the mean score of students' scores in mathematics learning addition and subtraction, namely ± 67,57.